2015
DOI: 10.1161/atvbaha.114.303817
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma S-Adenosylhomocysteine–Accelerated Atherosclerosis Is Associated With Epigenetic Regulation of Endoplasmic Reticulum Stress in apoE −/− Mice

Abstract: Objective-S-Adenosylhomocysteine (SAH) is a better predictor of cardiovascular disease than homocysteine is, and it has been implicated in mediating the pathogenicity of hyperhomocysteinemia in atherosclerosis via an epigenetic mechanism. However, the underlying mechanism remains unclear. Here, we tested the hypothesis whether the effect of SAH on atherosclerosis is involved in epigenetic regulation of endoplasmic reticulum stress. Approach and Results-A total of 48 apolipoprotein E-deficient mice at 8 weeks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 54 publications
0
32
1
Order By: Relevance
“…The promoter activity of GRP78 has been shown to be mediated through epigenetic regulation [18,19]. We did not find evidence for this activity, but histone modification or DNA methylation may be involved in neurite elongation and cell survival via upregulation of GRP78 expression.…”
Section: Resultscontrasting
confidence: 60%
“…The promoter activity of GRP78 has been shown to be mediated through epigenetic regulation [18,19]. We did not find evidence for this activity, but histone modification or DNA methylation may be involved in neurite elongation and cell survival via upregulation of GRP78 expression.…”
Section: Resultscontrasting
confidence: 60%
“…Elevated homocysteine in plasma is an independent risk factor for cardiovascular diseases [5]. We and others have suggested that SAH is a key mediator of homocysteine-associated atherogenesis [1,6,7]. Our previous studies show that SAH can induce endothelial cell dysfunction and activation by decreasing nitric oxide production and increasing oxidative stress and leukocyte adhesion [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…This might be mediated by SAH-reduced occupancy of 3meH3K4 at the promoters of these genes. In contrast, Xiao et al (2015) observed no effect of plasma SAH accumulation on 3meH3K4 in an animal model of atherosclerosis. Furthermore, Esfandiari et al (2010) reported that elevated hepatic SAH levels were associated with decreased occupancy of 3meH3K9 at the promoters of ER stress-related genes in mice with alcoholic liver injury.…”
Section: Epigenetic Mechanismmentioning
confidence: 65%
“…They found early atherosclerotic lesion areas were also increased in these mice. Next, Xiao et al (2015) treated apoE−/− mice at 8 weeks with SAHH inhibitor and shRNA for an additional 16 weeks and found increased plasma SAH G Model No. of Pages 9 concentrations and accelerated the development of atherosclerotic lesion areas in both groups of mice.…”
Section: Sah and Atherosclerosismentioning
confidence: 99%